Implementação de ações de vigilância epidemiológica em nível regional The implementation of epidemiological surveillance actions at regional level - Tânia Cristina de Oliveira (Universidade de São Paulo, 1989)
Relata-se experiência de reorganização dos serviços de Vigilância Epidemiológica, em nível regional, no Centro Regional de Saúde de Governador Valadares, MG, Brasil, durante o ano de 1985, com o objetivo de propor algumas medidas que possam contribuir para o aumento da remessa de informações pelo nível local. An attempt at a reorganization of the Epidemiological Surveillance Service at regional level in the Central Health Region of Governador Valadares, MG, Brasil, undertaken during 1985 is reported on. This study discusses simple measures that may be taken with a view to increasing interest in Epidemiological Surveillance actions at the local level and emphasizes the fact that the of data to the local level is essential to this interest.